Diseño e implementación de un sistema de gestión de calidad basado en la ISO 9001:2008 para el área de operaciones del sistema integrado de seguridad ECU911 de la ciudad de Machala. - Pineda Zambrano, Betsy del Carmen (2015)
In research conducted in the area of ​​operations of the Integrated Security System ECU911 city of Machala, several problems were identified in the area of ​​video surveillance; where employees who work in the video room surveillance are increasingly demanding, as such processes are required with characteristics that meet their expectations and therefore the direct beneficiaries of the service provided by the institution to the citizens of the province of El . gold is why we must work towards total customer satisfaction through a process of continuous improvement and implement standardized guidelines for maximum quality service offered; why was the need to implement the project entitled "Design and Implementation of a quality management system based on ISO 9001: 2008. area for integrated security operations ECU911 city of Machala system" When starting the project an investigation of the processes that existed at that time in the area of ​​video surveillance, then corrective actions and new processes are performed; Likewise the implementation of policies and document control to carry a standard and orderly manner the processes needed for a good room procedure was performed video. ISO 9001 was used for this work degree: 2008 because it is focused on processes that are adaptable to any institution and allows you to provide services that meet the requirements of users. For the above stated is concluded that with the implementation of ISO 9001: 2008 in the Integrated Security System ECU 911, allowed for processes that reduced the risk of misuse and unauthorized information output by the responsible personnel.